PEMBATALAN PERKAWINAN YANG DALUWARSA MENURUT UNDANG-UNDANG PERKAWINAN DAN KHI (PUTUSAN NOMOR 406/PDT.G/2020/PA.BATG) - Hartanti Widiastuti; Setyaningsih (Reformasi Hukum Trisakti, 2022)
A marriage may be dissolved if it does not adhere to the pillars and legal conditions, according to Article 22 of the UUP. In the Bantang Religious Court Decision Number 406/Pdt.G/2020/PA, not all requests for annulments of expired marriages are turned down.Syamsir bin H. Harsa did not adhere to Article 9 UUP, so the judge concurred. The question is whether the Judge in his decision said in the Decision Number 406/Pdt.G/2020/PA that a marriage that has been in existence for a longer period of time than specified in that decision can be dissolved. Concerning cancellation, BTG Do the Compilation of Islamic Law and Law No. 1 of 1974 both apply to marriage? Normative law research methods are descriptive and analytical. Results of the study, discussion and findings; a marriage that has been legally consummated after the deadline in this decision has passed cannot be canceled because it does not comply with Article 2 UUP because the marriage was not registered at the KUA with Article 2 UUP. Regarding the deadline for filing an annulment, the judge's ruling in this case does not follow Article 27 paragraph (3) UUP and Article 72 paragraph (3) KHI.